Community Economic Innovation in Mangrove Area at East Beach of Java Island - Ervina Wahyu Setyaningrum; Zulis Erwanto; Kanthi Pangestuning Prapti; Annastia Loh Jayanti (Budapest International Research and Critics University, 2020)
Banyuwangi is in a position that is very strategic that have potential include prospective tourism and business vehicles in the form of a crossing port to the Bali, loading port of goods, beach tourism, Ijen Mountain tours and Mangrove Forests. At Cemara Beach, there are about 11 types of Mangroves whose density is still lacking. Even though around it there are ponds, as well as the landing place to lay eggs. In relation to the living conditions of coastal communities, one important aspect of strengthening Mangrove conservation is to involve and seek local community support. The existence of Mangrove areas is expected to reduce sedimentation. This research was conducted on the east coast of Java Island, namely Cemara Beach, which is located in Rowo Village, Pakis Sub-district, Banyuwangi District, Banyuwangi Regency, East Java, Indonesia in 2020. The results of the study show: a) The Community is able to deal with change and technological innovation overcome the negative impact of the development of special interest tourism as a center for Mangrove processing production, Mangrove nurseries, turtle conservation, Cemara forest; b) The ability of the community has increased sufficiently in entrepreneurship based on Mangrove potency on the Cemara beach; c) Partner communities are able to plan integrated and sustainable management of areas that will be used as the basis for implementing physical development, spatial facilities, and special interest tourism infrastructure.